The Different Roles of Glucocorticoids in the Hippocampus and Hypothalamus in Chronic Stress-Induced HPA Axis Hyperactivity - Zhu, Li-Juan; Liu, Meng-Ying; Li, Huan; Liu, Xiao; Chen, Chen; Han, Zhou; Wu, Hai-Yin; Jing, Xing; Zhou, Hai-Hui; Suh, Hoonkyo; Zhu, Dong-Ya; Zhou, Qi-Gang (PLOS ONE, 2014)
Hypothalamus-pituitary-adrenal (HPA) hyperactivity is observed in many patients suffering from depression and the mechanism underling the dysfunction of HPA axis is not well understood. Chronic stress has a causal relationship with the hyperactivity of HPA axis. Stress induces the over-synthesis of glucocorticoids, which will arrive at all the body containing the brain. It is still complicated whether glucocorticoids account for chronic stress-induced HPA axis hyperactivity and in which part of the brain the glucocorticoids account for chronic stress-induced HPA axis hyperactivity. Here, we demonstrated that glucocorticoids were indispensable and sufficient for chronic stress-induced hyperactivity of HPA axis. Although acute glucocorticoids elevation in the hippocampus and hypothalamus exerted a negative regulation of HPA axis, we found that chronic glucocorticoids elevation in the hippocampus but not in the hypothalamus accounted for chronic stress-induced hyperactivity of HPA axis. Chronic glucocorticoids exposure in the hypothalamus still exerted a negative regulation of HPA axis activity. More importantly, we found mineralocorticoid receptor (MR) - neuronal nitric oxide synthesis enzyme (nNOS) - nitric oxide (NO) pathway mediated the different roles of glucocorticoids in the hippocampus and hypothalamus in regulating HPA axis activity. This study suggests that the glucocorticoids in the hippocampus play an important role in the development of HPA axis hyperactivity and the glucocorticoids in the hypothalamus can't induce hyperactivity of HPA axis, revealing new insights into understanding the mechanism of depression.